THE ROLE OF RELIGIOSITY AND LONELINESS ON QUARTER LIFE CRISIS IN STUDENTS OF MUHAMMADIYAH UNIVERSITY OF SIDOARJO (UMSIDA) - Rachma, Khasyya Aulia; Ghozali Rusyid Affandi; Hidayatulloh (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: Quarter Life Crisis is a state of feeling that arises when individuals reach their twenties, where they will feel worried about the future, especially related to work and the surrounding environment. This correlational quantitative research aims to analyze the role of religiosity and loneliness on quarter life crisis. Method: This study involved a sample of 263 respondents, by applying accidental sampling technique. The instrument used in this study is to use three psychological scales namely the quarter life crisis scale, religiosity scale and loneliness scale. The data analysis technique used in this study is multiple linear regression with the IBM SPSS version 26.0 program for windows. Results: The results of this study, that there is a significant role between religiosity and loneliness on quarter life crisis, which is 23%. Then, there is a negative role between religiosity on quarter life crisis and there is a positive role between loneliness on quarter life crisis. Novelty: In particular, this study tries to combine two variables (X), namely Religiosity and Loneliness, to see the contribution of these two variables to the phenomenon that is experienced by many early adult individuals or students, namely Quarter Life Crisis.